Distributed discrete-event modeling and simulation using CLOWN - Azucena, Ric L (2004)
Simulation is the process by which understanding of the behavior of an already existing or to be constructed physical system is obtained by observing the behavior of a model representing a system. Simulations are among the most computationally intensive computer applications. Complex real-word problems often lead to complex models that generate high volumes of data. Thus, the need for distributed simulation system is growing as the modeling of real world systems seem to require intractable mathematical processes and may take significant amount of time. CLOWN (Concatenated LOcal-area and Wide-area Network) is an object-oriented discrete-event simulation environment where models are built using a library of predefined and user defined network objects. This object oriented simulation tool was created in discrete components using object-oriented C language that support a particular application programming interface. Modifying CLOWN API and design so that modules or components can be distributed to different machine during execution is one of the goal of this paper. The group has developed a graphical user interface that can aid the CLOWN users, specifically in modeling, coding and verification state of the system simulation, and execution with automatic code generator. As compared before, to be able to use the CLOWN, we have to use any modeling tool (ex. Poseidon) to model the project. Then, the whole source code would be edited using any editor available before proceeding to verification. With this, the newly created GUI for CLOWN essentially offers a simple straightforward solution to the problem.